Efficacy of Group Work as Teaching Strategy in Developing Skills among Higher Learning Institution Students in Tanzania - Kinyaduka, Bryson Daudi (Nurture, 2025)
The paper sought to establish the efficacy of group work teaching strategy in developing various skills/capabilities among higher learning institution students in Tanzania. The study adopted exploratory sequential design. The study employed Focus Group Discussion to collect qualitative data in phase one. It used questionnaire to gather quantitative data in phase two. The sample size was 381 of whom 24 were student participants obtained through maximum variation sampling technique and 357 were student respondents obtained through convenience sampling teachnique. Interview guide and questionnaire were used to collect data in phase one and phase two, respectively. Data analysis techniques used was content analysis and Yeh’s Index of Satisfaction. Content analysis was used to analyse qualitative data. Yeh’s Index of Satisfaction was used to analyse quantitative data. The study revealed group work had more capability of developing some skills, and less capability in developing others. Group work developed numerous skills/capabilities at different magnitude. As such, the efficacy in developing skills/capabilities was at 0.70 to 0.79 (High) and at 0.80 and above (very high) in higher learning institutions. Group work as a teaching strategy has the efficacy of developing numerous capabilities/skills from high to very high in higher learning institution. Therefore, higher learning institutions should continue to embrace the teaching strategy. It is indispensable to build capacity among instructors on how to apply the teaching strategy effectively.